2013
DOI: 10.1007/s00426-013-0507-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensory ERP effects in auditory distraction: did we miss the main event?

Abstract: Event-related potentials (ERPs) offer unique insights into processes related to involuntary attention changes triggered by rare, unpredictably occurring sensory events, that is, distraction. Contrasting ERPs elicited by distracters and frequent standard stimuli in oddball paradigms allowed the formulation of a three-stage model describing distractionrelated processing: First, the distracting event is highlighted by a sensory filter. Second, attention is oriented towards the event, and finally, the the task-opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 36 publications
11
40
1
Order By: Relevance
“…The long tone duration was 750 ms in all three conditions, whereas short tone duration was 150, 300, or 450 ms. As in previous studies (Horváth, 2014(Horváth, , 2016, tone offsets were followed by a consistent positive-negative (P1-N1) waveform pattern most distinctly observable at the temporal leads in both groups, which, in combination with the fact that offset-related waveforms peaked about 50 ms later than the typical onset-related P1-N1 waveforms, may indicate that these offset-related waveforms reflected mainly the T-complex (Wolpaw and Penry, 1975) of the auditory ERP. Although the fronto-centrally peaking onset-related P1-N1 waveform was larger in the older adult group in correspondence with most previous studies (see Introduction), no significant between-group differences were found for the offset-related P1, or the temporally measured offset-related N1.…”
Section: Tone Offset-related Processingsupporting
confidence: 78%
See 3 more Smart Citations
“…The long tone duration was 750 ms in all three conditions, whereas short tone duration was 150, 300, or 450 ms. As in previous studies (Horváth, 2014(Horváth, , 2016, tone offsets were followed by a consistent positive-negative (P1-N1) waveform pattern most distinctly observable at the temporal leads in both groups, which, in combination with the fact that offset-related waveforms peaked about 50 ms later than the typical onset-related P1-N1 waveforms, may indicate that these offset-related waveforms reflected mainly the T-complex (Wolpaw and Penry, 1975) of the auditory ERP. Although the fronto-centrally peaking onset-related P1-N1 waveform was larger in the older adult group in correspondence with most previous studies (see Introduction), no significant between-group differences were found for the offset-related P1, or the temporally measured offset-related N1.…”
Section: Tone Offset-related Processingsupporting
confidence: 78%
“…As in previous studies (e.g., Berti and Schröger, 2001;Horváth, 2014Horváth, , 2016Volosin and Horváth, 2014), tone onsets were preceded by a negative-going ERP trend, suggesting that participants exploited the constant SOA to prepare for the tones. Tone onsets elicited the succession of P1, N1 and P2 waveforms, which were superimposed on the negative trend.…”
Section: Erpssupporting
confidence: 75%
See 2 more Smart Citations
“…The empirical contribution by Horváth (2014) rounds up the focus on attentional capture by task-irrelevant auditory signals. By means of event-related brain potentials (ERPs), the author investigates characteristics of the attentional orienting and reorienting processes assumed to underlie behavioral distraction by unexpected sounds.…”
mentioning
confidence: 99%